Determine Dispersion Coefficient of 85Rb Atom in the Y–Configuration - Dung, Nguyen Tien (VNU Journal of Science: Mathematics - Physics; Vol 35 No 2DO - 10.25073/2588-1124/vnumap.4352, 2019)
Abstract : In this work, we derive analytical expression for the dispersion coefficient of 85 Rb atom for a weak probe laser beam induced by a strong coupling laser beams. Our results show possible ways to control dispersion coefficient by frequency detuning and of the coupling lasers. The results show that a Y-configuration appears two transparent window of the dispersion coefficient for the probe laser beam. The depth and width or position of these windows can be altered by changing the intensity or frequency detuning of the coupling laser fields. Keywords: Electromagnetically induced transparency, dispersion coefficient. References [1] R.W. Boyd, Slow and fast light: fundamentals and applications, J. Mod. Opt. 56 (2009) 1908–1915. [2] J. Javanainen, Effect of State Superpositions Created by Spontaneous Emission on Laser-Driven Transitions, Europhys. Lett. 17 (1992) 407. [3] M. Fleischhauer, I. Mamoglu, and J. P. Marangos, Electromagnetically induced transparency: optics in coherent media, Rev. Mod. Phys. 77 (2005) 633-673. [4] L.V. Doai, D.X. Khoa, N.H. Bang, EIT enhanced self-Kerr nonlinearity in the three-level lambda system under Doppler broadening, Phys. Scr. 90 (2015) 045502. [5] D.X. Khoa, P.V. Trong, L.V. Doai, N.H. Bang, Electromagnetically induced transparency in a five-level cascade system under Doppler broadening: an analytical approach, Phys, Scr. 91 (2016) 035401. [6] K.J. Boller, A. Imamoglu, S.E. Harris, Observation of electromagnetically induced transparency, Phys. Rev. Lett. 66 (1991) 2593. [7] S. Sena, T.K. Dey, M.R. Nath, G. Gangopadhyay, Comparison of Electromagnetically Induced Transparency in lambda, vee and cascade three-level systems, J. Mod. Opt. 62 (2014) 166-174. [8] Daniel Adam Steck, 85Rb D Line Data: http://steck.us/alkalidata (2013) (accessed 20 September 2013)